Stakeholder management in projects: A brief review - Gildemberg Alves dos Santos; Telma Lúcia de Andrade Lima; Suzana Candido de Barros (Universidade Estadual de Alagoas, 2023)
This article aims to conduct a systematic literature review on the management studies of stakeholders in project management, in the period between the years 2020 and 2021, in the field of articles deposited in the database of Journals of the Coordination for the Improvement of Higher Education Personnel (Capes). To this end, the protocol Main Items for Reporting Systematic Reviews and Meta-analyses (Prisma) was used for the selection of articles. The results indicate that since the release of the version "a first look at the PMBOK 7th edition guide, there are no articles in Portuguese that address stakeholder management from the perspective of the principles present in this version. Limitations of the study are considered the fact that the database of Capes journals presents limitations regarding the use of search engines. For future studies it is indicated that the theme be approached a systematic literature review using other databases.